The Relations of Nursing Clinical Teacher Effectiveness, Clinical Belongingness Sense, and Compassionate Competencies among Undergraduate Nursing Students: A Cross-Sectional Correlation Study - SIMA POURTEIMOUR; MOHAMMADALI HOSSEINI (Journal of Advances in Medical Education and Professionalism)
Introduction: Nursing teachers influence their students’ views and values, creating Compassionate Competence (CC) and Clinical Belonging Sence (CBS). Their work extends beyond technical abilities, as they foster empathy and community in order to provide good patient care. The purpose of this study was to examine the link between CC and CBS and Nursing Clinical Teacher Effectiveness (NCTE).Methods: This cross-sectional correlation study was conducted on 237 nursing students (response rate of 94.5%) selected using census sampling; the Belongingness Scale-Clinical PlacementExperience (BES-CPE), Compassionate Competence Scale, and Nursing Clinical Teacher Effectiveness Inventory were used to collect the data. The data were analyzed using descriptivestatistics, the Chi-square test, the Pearson correlation test, and the linear regression test in SPSS (ver.16).Results: Both discovered factors account for 21.4% of CC, with a positive connection with NCTE (r=0.392, P=0.001) and CBS (r=0.564, P=0.001). CBS and CC also showed a strong positive connection (r=0.424, P=0.001). NCTE can explain why CBS (31.42%) is nearly twice as high as CC (16.06%) among nursing students. NCTE teaching skill was positively connected with selfesteem(r=0.544, P=0.001), CBS efficiency (r=0.528, P=0.001), continuity (r=0.367, P=0.001), and CC insight (r=0.374, P=0.001). Interpersonal communication and personality qualities in NCTE had a moderate connection with efficiency (r=0.491, P=0.001) and self-esteem (r=0.468, P=0.001) in CBS. Furthermore, female students received considerably higher NCTE scores than male students (P=0.012).Conclusions: Continuous training for clinical faculty is essential for mentoring nursing students, improving their skills and attitudes toward quality patient care and instilling a sense of belonging and compassion.